Calcium oxide derived from eggshells supported on titanium oxide green catalysts for lignin hydrogenolysis under supercritical alcohol solvents. (April 2022) - Ma, Yangyang; Li, Hongji; Yang, Huiqing; Zhu, Yaodi; Zhao, Lijun; Li, Miaoyun
Abstract: Catalytic depolymerization of lignin has been investigated in the presence of egg shell derived CaO/TiO2 catalysts. Reaction was carried out for different reaction temperatures (250, 280 and 310 °C) at different reaction holding time at presence of N2 and H2 gas under ethanol, methanol and water solvent. Highest bio-oil yield was found with CaO/TiO2 -800 catalyst in ethanol solvent under N2 (74.8 wt%), and H2 (82.8 wt%) environment compared to the water solvent. Under hydrogen environment very less amount of unreacted residue was produced. Bio-oil analysis showed that in under nitrogen environment catalytic depolymerization of lignin produced alkyl phenolic monomer compounds 68.0% with methoxy phenolic compounds 24.0%. Interestingly hydrogen promoted the deoxygenating and hydrogenation reaction which produced higher cyclohexane compounds 38.2% and aromatic hydrocarbon 19%. This is suggesting that the effectively breaking of β-O-4 bond by the catalysts which has an excellence character for the industrial application. Elemental analysis shows that hydrogen enhanced the bio-oil quality compared to the nitrogen environment. This work introduces new perspectives for the efficient production of functional compounds from lignin assisted by egg shell derived green catalysts. Highlights: Egg shell derived CaO green catalysts were used for lignin depolymerization. Maximum bio-oil 82.8 wt% yield was found by CaO/TiO2 catalysts with H2 . Higher selective alkyl phenols and methoxy phenols was obtained under N2 gas. Catalyst CaO/TiO2 effectively hydrogenated bio-oil under H2 gas.